2020
DOI: 10.1111/vec.12944
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized, double‐blinded clinical study evaluating the efficacy and safety of bupivacaine versus morphine‐bupivacaine in caudal epidurals in cats with urethral obstruction

Abstract: Objective To investigate the efficacy and safety of the caudal epidural technique in cats with urethral obstruction (UO). Design Prospective, double‐blinded, randomized, sham‐controlled study. Animals Eighty‐eight male cats with UO. Interventions Thirty cats randomized to bupivacaine epidural (BUP), 28 cats to bupivacaine‐morphine epidural (BUP/MOR), and 30 cats to sham epidural (SHAM). Measurements and Main Results Time to perform the epidural and efficacy of the epidural was assessed by evaluation of tail an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In contrast, a study by Pratt et al (2020) described the use of 0.22 mg/kg of 0.5% bupivacaine (with or without morphine 0.1 mg/kg) administered into the sacrococcygeal epidural space in cats with urinary obstruction; this dose of bupivacaine corresponds to a volume of 0.044 mL/kg which is much lower than the volume used in our cats [ 5 ]. Pratt et al (2020) found that with this dose, the anaesthetic and analgesic requirements during urethral catheterization were decreased without any negative haemodynamic changes [ 5 ]. However, further studies need to be conducted to evaluate the extent of the epidural spread of the local anaesthetic when this lower volume is used via the sacrococcygeal route for pelvic limb orthopaedic procedures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, a study by Pratt et al (2020) described the use of 0.22 mg/kg of 0.5% bupivacaine (with or without morphine 0.1 mg/kg) administered into the sacrococcygeal epidural space in cats with urinary obstruction; this dose of bupivacaine corresponds to a volume of 0.044 mL/kg which is much lower than the volume used in our cats [ 5 ]. Pratt et al (2020) found that with this dose, the anaesthetic and analgesic requirements during urethral catheterization were decreased without any negative haemodynamic changes [ 5 ]. However, further studies need to be conducted to evaluate the extent of the epidural spread of the local anaesthetic when this lower volume is used via the sacrococcygeal route for pelvic limb orthopaedic procedures.…”
Section: Discussionmentioning
confidence: 95%
“…The sacrococcygeal epidural has been described for urethral catheterization in cats with urinary obstruction [5]. Otero et al (2015) mention the use of sacrococcygeal epidurals for perineal or hind limb surgical procedures in cats, but they do not describe the perioperative analgesic or haemodynamic response [6].…”
Section: Introductionmentioning
confidence: 99%
“…128 Sacrococcygeal epidural anaesthesia has been used as an alternative to lumbosacral epidural injections for cats with urethral obstruction (Figure 14). 129,130 A sacrococcygeal technique using bupivacaine or bupivacaine/morphine reduced propofol requirements and extended the time to rescue analgesia in these cats. 129 Anatomical and ultrasonographic studies have shown that the depth of needle insertion for sacrococcygeal epidural anaesthesia is approximately 0.6 cm in cats, whereas the distance between skin and the ligamentum flavum is 1 cm at the lumbosacral space.…”
Section: Local Anaestheticsmentioning
confidence: 99%
“…129,130 A sacrococcygeal technique using bupivacaine or bupivacaine/morphine reduced propofol requirements and extended the time to rescue analgesia in these cats. 129 Anatomical and ultrasonographic studies have shown that the depth of needle insertion for sacrococcygeal epidural anaesthesia is approximately 0.6 cm in cats, whereas the distance between skin and the ligamentum flavum is 1 cm at the lumbosacral space. 131 The epidural space is small in cats but the technique can provide excellent perioperative analgesia and be performed safely.…”
Section: Local Anaestheticsmentioning
confidence: 99%
“…Caudal epidural blocks should be considered and may facilitate catheterisation, while also providing analgesia to a traumatised urinary tract following the procedure. Blocks have been shown to be safe, and they can reduce the volume of anaesthetic drugs and provide prolonged postprocedural analgesia (Pratt and others 2020). An excellent review and detailed step‐by‐step guide on how to perform this technique has been published by O'Hearn and Wright (2011).…”
Section: Before Catheterisationmentioning
confidence: 99%